The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1472-6963-14-64
|View full text |Cite
|
Sign up to set email alerts
|

Local psychiatric beds appear to decrease the use of involuntary admission: a case-registry study

Abstract: BackgroundStudies on the effect of organizational factors on the involuntary admission of psychiatric patients have been few and yielded inconclusive results. The objective was to examine the importance of type of service-system, level of care, length of inpatient stay, gender, age, and diagnosis on rates of involuntary admission, by comparing one deinstitutionalized and one locally institutionalized service-system, in a naturalistic experiment.Methods5538 admissions to two specialist psychiatric service-areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Prior research has shown that the use of coercion varies both within and between jurisdictions [ 12 - 14 ]. Differences and changes in health care organisation and financing, legislation, socio-demographic characteristics, diagnostic patterns and patient characteristics play important roles in explanations of such variations, but findings are inconclusive [ 6 , 15 - 17 ] Differences within countries also suggest that local treatment cultures and staff attitudes towards coercive measures may contribute to variations [ 14 , 18 ]. In a multilevel analysis of attitudes to coercion, some differences among wards were found, but most variance could be attributed to individual staff level factors within wards [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that the use of coercion varies both within and between jurisdictions [ 12 - 14 ]. Differences and changes in health care organisation and financing, legislation, socio-demographic characteristics, diagnostic patterns and patient characteristics play important roles in explanations of such variations, but findings are inconclusive [ 6 , 15 - 17 ] Differences within countries also suggest that local treatment cultures and staff attitudes towards coercive measures may contribute to variations [ 14 , 18 ]. In a multilevel analysis of attitudes to coercion, some differences among wards were found, but most variance could be attributed to individual staff level factors within wards [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have touched upon the idea that services characteristics affect the use of involuntary admissions (Huxley & Kerfoot, 1993;Wierdsma & Mulder, 2009;Lay et al 2011). Recent Norwegian studies (Myklebust et al 2014) found that patients from a deinstitutionalised system were more likely to be involuntarily admitted then the ones in the locally institutionalised service-systems. Recent Norwegian studies (Myklebust et al 2014) found that patients from a deinstitutionalised system were more likely to be involuntarily admitted then the ones in the locally institutionalised service-systems.…”
Section: Introductionmentioning
confidence: 99%
“…[13] 3.1.2 Health system outcomes In the Scandinavian country of Norway, a decreased involuntary admission was associated with male sex, psychotic disorders and local health care system as evidenced by the decreased number of involuntary admissions with more available local beds. Myklebust, Sorgaard and Wynn [25] explained that the proximity and local control of psychiatric beds and availability of psychiatric care in the local area help the individuals seek care and management before any worsening of condition occur. This also helps clinicians to more easily follow-up patients.…”
Section: Presentationmentioning
confidence: 99%